ANALISIS PENGARUH UKURAN PERUSAHAAN, STRUKTUR KEPEMILIKAN DAN RASIO PERPUTARAN PERSEDIAAN TERHADAP PEMILIHAN METODE PERSEDIAAN PADA PERUSAHAAN MANUFAKTUR GO PUBLIC DI BEI TAHUN 2006 – 2010 - Linda Santioso; Stella Halim (Jurnal Akuntansi, 2013)
AbstractThe objective of this research is to examine and give the empirical evidence of differences between FIFO and Average by factors that influences such as firm size, capital structure, and inventory intensity. The objects of this research are manufacturing industries listed at the Jakarta Stock Exchange before 2006. Time period are 5 years from 2006 to 2010. By using 42 companies sample are 8 FIFO company’s and 34 Average company’s using purposive sampling method. Mann Whitney and Logistic Regression were used to test this hypothesis. This research found that no differences between FIFO company and Average company for capital structure and inventory intensity. Only one independent variable is firm size that influences selection inventory valuation method FIFO or Average.Keywords: Inventory Valuation Method, FIFO, Average, Firm Size, Capital Structure, and Inventory Intensity.